El turismo en el Perú: Historia, cadena y problemáticas - Armas Asín, Fernando (2024)
The text develops, within the framework of the construction of tourist activity, how it was organized and the role that the entities involved had, reviewing the literature on the matter. It is concluded that tourism as an economic sector was built from various global and local events that affected demand and supply, highlighting the nature of the business chain formed. This text also addresses and delimits problems that have affected tourist activity in the past and affect it still. The study can help to better understand this economy and social activity today.